Manajemen Strategi Kepemimpinan Transformasional Nilai di Pondok Modern Darussalam Gontor - Attamimi, Munif; Ibrahim, Abdullah; Wijoyo, Suparto; Suyanto, Bagong (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
The purpose of this study is to analyze the strategies implemented, the factors that influence them, and the challenges faced in efforts to shape the leadership character of santri in the pesantren environment. This study used a qualitative approach with a case study method to understand transformational leadership strategies at Pondok Modern Darussalam Gontor. The results of the study show that leadership education for santri at Pondok Modern Darussalam Gontor is carried out through role modeling, experience-based learning, and collective and participatory leadership. Factors that support the success of leadership education in Islamic boarding schools include the role modeling of kiai and ustaz, the santri regeneration system, a culture of discipline and independence, and an environment that supports leadership learning. Challenges faced in implementing leadership education in Islamic boarding schools include rapid technological developments, limited access to modern leadership insights, economic and social disparities, and resistance to change within the Islamic boarding school environment.